Prevalence and Influencing Factors of Overweight and Obesity among Adult Residents of Western China: A Cross-Sectional Study. (13th October 2021) - Zheng, Li; Deng, Feng; Wang, Honglin; Yang, Biao; Qu, Meng; Yang, Peirong
Abstract : Background . Overweight and obesity have become a serious health problem. There are a few data on the prevalence of overweight and obesity in Baoji city of western China, this study was conducted to investigate the epidemiologic features of overweight and obesity and explored influencing factors among Baoji adult residents. Methods . A cross-sectional study, including 36, 600 participants aged above 15 years, was carried out in Baoji city in 2018. Each participant's weight and height were measured, and demographic and behavioral characteristics were collected using questionnaires. Data were analyzed by means of logistic regression considering 95% level of significance. Results . Overall, the prevalence of overweight and obesity was 30.73% and 3.11%, respectively. Male had a significantly higher prevalence of overweight (31.45% vs. 29.98%, P < 0.05 ) while female had a higher prevalence of obesity (3.50 vs. 2.74, P < 0.001 ). In the logistic regression analysis, being married or living with a partner (OR = 1.266, P < 0.001 ), unemployed or retired (OR = 1.183, P < 0.001 ), former smokers (OR = 1.116, P < 0.05 ), drinking alcohol (OR = 1.410, P < 0.001 ), sleeping more than 10 hours (OR = 1.274, P < 0.001 ), and increasing age were all significantly associated with a higher prevalence of overweight/obesity, whereas people who lived in rural areas (R = 0.904, P < 0.001 ) or had a sufficient leisure time physical activity per week (R = 0.945, P < 0.05 ) were associated with a lower prevalence. Conclusion . Our results demonstrate that demographic and behavioral factors play an important role in prevalence of overweight/obesity, which can support the implementation of interventions aimed at weight control and consequently prevention of related diseases in this population.